Narratives Of Ecological Equilibrium in Jostein Gaarder’s Anna’s World: A Fritjof Capra Perspective - Jein Palilati; Herson Kadir; Herman Didipu (Universitas Islam Negeri Palopo, 2026)
This study addresses a gap in ecocritical scholarship that has predominantly focused on ecological destruction and crisis narratives, with limited attention to how literary works construct positive visions of human–nature equilibrium. Drawing on Fritjof Capra's ecological framework, this research examines the narrative of human–nature equilibrium in Jostein Gaarder's novel Anna's World. Using a descriptive-qualitative approach and Miles, Huberman, and Saldaña's interactive model of analysis, the study identifies six ecological principles within the novel: networks, cycles, solar energy, partnerships, diversity, and dynamic balance. The findings demonstrate that Anna's World systematically constructs a narrative of harmonious human–nature relations rather than merely critiquing environmental damage. By shifting analytical attention from ecological crisis toward equilibrium narratives, this study contributes to literary ecology and ecocriticism, offering a framework for reading literature as a medium for ecological consciousness transformation.